2021
DOI: 10.1038/s41598-021-00248-z
|View full text |Cite
|
Sign up to set email alerts
|

Fungal infections lead to shifts in thermal tolerance and voluntary exposure to extreme temperatures in both prey and predator insects

Abstract: Pathogens can modify many aspects of host behavior or physiology with cascading impacts across trophic levels in terrestrial food webs. These changes include thermal tolerance of hosts, however the effects of fungal infections on thermal tolerances and behavioral responses to extreme temperatures (ET) across trophic levels have rarely been studied. We examined how a fungal pathogen, Beauveria bassiana, affects upper and lower thermal tolerance, and behavior of an herbivorous insect, Acyrthosiphon pisum, and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Across systems, host heat tolerance can be influenced by infection status ( table 1 ). The underlying mechanisms driving these changes remain largely unexplored [ 14 , 21 ]. Given the wide range of host–parasite interactions that have similar responses, there could be multiple underlying mechanisms.…”
Section: Host Heat Tolerance During Infection: What Mechanisms Could ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Across systems, host heat tolerance can be influenced by infection status ( table 1 ). The underlying mechanisms driving these changes remain largely unexplored [ 14 , 21 ]. Given the wide range of host–parasite interactions that have similar responses, there could be multiple underlying mechanisms.…”
Section: Host Heat Tolerance During Infection: What Mechanisms Could ...mentioning
confidence: 99%
“…Parasites can significantly contract host heat tolerance during extreme warming events (e.g. [ 18 , 19 , 21 , 23 ]). Reduced tolerance to heating is therefore an intrinsic component of the virulence—harm caused by infection (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…1A, logRR>0, RR=1.47, p=0.0046). Previous findings that infection can reduce the ability of hosts to tolerate elevated temperatures [16,43,44] may reflect this increase in pathogen virulence.…”
Section: Resultsmentioning
confidence: 99%
“…1). Under this rationale, recent studies with small insects have shown that some individuals may actually explore voluntarily extreme hot or cold temperatures, and even engage in thermal risks (NAVAS; AGUDELO-CANTERO; PORRAS et al, 2021). The latter has been termed thermal boldness by in an investigation with fruit flies (D. melanogaster).…”
Section: What About Spatial Thermal Variations? the Role Of Behavior ...mentioning
confidence: 99%
“…Such scenario is even more critical for small ectothermic animals like many insects 3,37,41 , given constraints posed by a small body size (see above). However, small motile insects may also exhibit alternative behaviors when navigating in extreme thermal landscapes (ETLs), including the volunteer exploration of extreme temperatures and thermal risk-taking (namely thermal boldness) 42,43 . Moreover, thermal boldness towards extreme high temperatures may bear little dialog with acute heat tolerance, thus departing from any expectation based on optimality models of thermal adaptation (see Fig.…”
Section: Introductionmentioning
confidence: 99%